The Behaviour of Economic Agent in Islam - al Hakim, Muhammad Hanif (IAIN Ponorogo, 2019)
Abstract: Some notable economists believe that Economics is of normative science, which always focuses on the 'what should be' statement. Therefore it is included in the science of ethics, considering that it discusses an attitude of an individual in economic activity. Unfortunately, modern economics born from the womb of Western Civilization was influenced by Utilitarianism which is undoubtedly contradictary to Islam. This certainly will create problems in the future for Muslims, especially in economic activities both on an individual and social scale. This article will discuss how the behavior of an economic agent should be viewed by Islam. This research is qualitative in nature, using the methos of literature survey. The results of the study show that the correct understanding of Islam, the worldview of Islam, and the true nature of human beings and their actions will keep Muslim behavior as an economic agent from being trapped into un-Islamic behavior in economic activities. الملخص: اعتقد بعض الاقتصاديين البارزين أن الاقتصاد هو نوع من العلوم المعيارية، والذي يركز دائمًا على عبارة